(untitled) (Journal of Parents and Teachers, 1996)
Children’s programming should consider the opinions of children, who demand more representation and quality content. UNICEF highlights the importance of reflecting the cultural diversity and experiences of young people in the media. The influence of television on children’s attitudes requires a responsible approach to content.